Extraction of a novel water-soluble gum from nettle (Urtica dioica) seeds: Optimization and characterization - Kutlu, Goezde; Bozkurt, Fatih; Tornuk, Fatih (ELSEVIER, 2020)
Nettle seed gum (NSG) which is a novel potential source of hydrocolloid was characterized in terms of yield, physicochemical, rheological, functional and thermal properties. According to Response Surface Methodology, the maximum extraction yield was determined as 6.17% on dry basis. In order to clarify the structural information of the gum, the FT-IR analysis and monosaccharide composition determination were performed. In the results, the NSG had 8.48% moisture, 10.81% total ash, 2.89% total protein, 1.15% total oil and 76.67% total carbohydrate. The FT-IR analysis revealed the existence of carboxyl groups, which gives the gum the capability of ion binding. Furthermore, Mannose/Galactose ratio was calculated as 1.07, indicating the water solubility of gum. DSC analysis showed that the NSG was highly stable in thermal process. Intrinsic viscosity, average viscosity and molecular weight values were determined as 8.56 +/- 0.4 dL/g and 1.89 +/- 0.1 x 10(6) g/mol, respectively. The emulsification capacity, emulsion stability and foam formation capacity of the NSG were 48%, 40% and 4%, respectively. The NSG exhibited shear thinning behavior while dynamic rheological analysis indicated the NSG had viscoelastic properties and G ' (the storage modulus) was higher than G '' (the loss modulus). In conclusion, the present study supplied novel knowledge on the NSG, which will be inestimable for clarifying its matchless functional properties. (c) 2020 Elsevier B.V. All rights reserved.
Keywords: Galactomannan; Response Surface Methodology; Nettle gum; SHEAR-FLOW BEHAVIOR; PHYSICOCHEMICAL CHARACTERIZATION; STRUCTURAL-CHARACTERIZATION; RHEOLOGICAL CHARACTERISTICS; FUNCTIONAL-PROPERTIES; CHEMICAL-COMPOSITION; INTRINSIC-VISCOSITY; XANTHAN GUM; L.; PURIFICATION; Biochemistry & Molecular Biology; Chemistry; Polymer Science